Comparing the optical and mechanical properties of PEKK polymer when CAD/CAM milled and pressed using a ceramic pressing furnace. (January 2019) - Alsadon, Omar; Wood, Duncan; Patrick, David; Pollington, Sarah
Abstract: The aim was to optimise the hot pressing parameters for processing PEKK polymer using a standard ceramic pressing furnace and compare the optical and mechanical properties of pressed samples to PEKK samples produced via CAD/CAM milling. The samples were compared using a spectrophotometer to determine the CIE L*a*b* colour values and ΔE colour difference. A universal testing machine was used for biaxial flexural strength testing and Vickers Hardness machine for measuring the hardness. It was concluded that hot pressed and milled PEKK samples showed no significant difference in the colour values, biaxial flexural strength or hardness.